Ligands for oral delivery of peptides across the blood-brain-barrier - Murad Al Gailani; Mengyang Liu; Jingyuan Wen (Compuscript Ltd, 2022)
Peptides are short chains of amino acids linked by peptide bonds. Many peptides and proteins are limited by their poor enzymatic stability and permeability across the intestinal epithelial membranes and/or blood-brain barrier (BBB). Parenteral administration of these peptides is unfavorable because of procedural complications and low patient compliance with treatments. Instead, oral delivery is the preferred route of administration because it allows for self-administration and has a high degree of patient acceptability and compliance. Oral delivery of these peptides poses a major challenge, because the peptide drug must overcome both the physical and biochemical barriers of the gastrointestinal tract and BBB. An oral drug delivery system is beneficial because it can protect peptide drugs against degradation and deliver them to the brain, where they exert their pharmacological actions. The use of active-targeting ligands and/or cell-penetrating peptides increases penetration and uptake across the BBB. This review focuses on the diverse combinations of drug delivery systems, active-targeting ligands, and cell-penetrating peptides used to deliver peptides to the brain.